Responses of Stomatal Characteristics to Environmental Factors in Fabaceae Trees of the Urban Forest in Maros Regency - Yahya, Roslina Yahya; Sukri, Hadija; Nirawati; Djarot, Ira Nurhayati Djarot (Forestry Department, University of Muhammadiyah Makassar, 2025)
The response of plants to environmental conditions is reflected in their stomatal characteristics, including stomatal type, number, and density. This novel research examines the influence of environmental factors on the stomatal characteristics of Fabaceae tree leaves in the Urban Forest of Maros Regency. The study explores the relationship between stomatal traits and environmental variables such as light intensity and air humidity. Data analysis employed Pearson correlation to assess how these variables affect stomatal number and density. The results reveal variations in stomatal types among Fabaceae species: Acacia exhibits diacytic stomata, Dadap Merah (Erythrina crista-galli L) has paracytic stomata, Trembesi shows normocytic stomata, and Sengon (Paraserianthes falcataria L) displays cyclocytic stomata. The study also finds that stomatal number and density are higher in the eastern region compared to the western region. Sengon exhibits the highest stomatal number and density among the species studied, whereas Dadap Merah has the lowest. Correlation analysis indicates that only the External Light Intensity of the Stand (ELIS) significantly affects stomatal number and density at the 0.05 (5%) level. Air humidity does not show a significant impact. These findings highlight the role of light intensity in shaping stomatal characteristics in Fabaceae trees within urban forests, contributing to a deeper understanding of plant-environment interactions and their ecological implications.